PREVALENCE OF DEPRESSION AND ITS ASSOCIATED FACTORS AMONG HIGH SCHOOL TEACHERS IN DIR(L) KPK, PAKISTAN - Zahid Khan; Kamal Ali Shah; Khawla Afzal; Sajjad Khan; Alweena Khan (Spectrum of Engineering Sciences, 2025)
In the present study, the prevalence of depression and its associated factors among high school teachers in district Lower Dir, KPK is investigated. Cluster random sampling is used to identify the representative sample from the population. A total of 180 teachers are selected from the study area. Their depression level is measured by scale (Centre for Epidemiological Studies Depression Scale Short Form, or CESD-10). A structured questionnaire is used for data collection. The data is presented by frequency distribution. The linear regression model is applied to assess the dependency of prevalence of depression on its risk factors. The model identifies only one variable out of ten (gender, age, residence, education level, income, marital status, chronic illness, workload, family support) variables, family support which is responsible for prevalence of depression. This indicates that in the study area, lack of family support is the major risk factor for incidence of depression.